2020
DOI: 10.1016/j.nuclphysb.2020.114975
|View full text |Cite
|
Sign up to set email alerts
|

Photon orbits and phase transitions in Born-Infeld-dilaton black holes

Abstract: Relations between photon orbits and thermodynamical phase transitions are explored in Born-Infeld-dilaton-AdS black hole. The coupling between the electromagnetic field and the dialton field is chosen such that the full phase diagram contains zeroth-order and first-order phase transitions as well as RPT. We find that there exist non-monotonic beahviors of the photon orbit radius rps and the minimum impact parameter ups which signal the existence of the various phase transitions. In particular, the marginal val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 104 publications
(117 reference statements)
0
8
0
Order By: Relevance
“…Now we are interested in exploring the relations between the shadow radius and phase transitions. According to [73,74,77,78], there is a close connection between black hole shadows and the black hole thermodynamics. Heat capacity is one of the interesting thermodynamic quantities which provides us with information related to thermal stability and phase transition of a thermodynamic system.…”
Section: A Relations Between Shadow Radius and Phase Transitionsmentioning
confidence: 99%
“…Now we are interested in exploring the relations between the shadow radius and phase transitions. According to [73,74,77,78], there is a close connection between black hole shadows and the black hole thermodynamics. Heat capacity is one of the interesting thermodynamic quantities which provides us with information related to thermal stability and phase transition of a thermodynamic system.…”
Section: A Relations Between Shadow Radius and Phase Transitionsmentioning
confidence: 99%
“…Based on the case studies in [38,39], it was found that the circular orbit radius of the photon can be a characteristic quantity to reflect the thermodynamic phase structure of a spherically symmetric black hole [40]. Related extensions can also be seen in [41,42]. The image of the black hole makes us think about whether it is possible to use the black hole shadow, which is observable, to reflect the thermodynamics of the black hole.…”
Section: Introductionmentioning
confidence: 99%
“…During the phase transition, these two parameters change by a finite amount, which serves as order parameters to characterise the black hole phase transition, with a critical exponent 1/2. Originally, this was observed in a charged AdS black holes [48], this correlation between gravity and thermodynamics, via photon orbits, can be seen in different black hole spacetimes, namely, Kerr-AdS [49], Born-Infeld AdS background [50], regular AdS black holes [51], massive gravity [52], Born-Infeld-dilaton black hole [53], fivedimensional Gauss-Bonnet black holes [54] etc. Related studies in other contexts have also appeared in subsequent works [55][56][57].…”
Section: Introductionmentioning
confidence: 99%